2021
DOI: 10.1098/rspb.2021.1626
|View full text |Cite
|
Sign up to set email alerts
|

Lifelong exposure to artificial light at night impacts stridulation and locomotion activity patterns in the cricketGryllus bimaculatus

Abstract: Living organisms experience a worldwide continuous increase in artificial light at night (ALAN), negatively affecting their behaviour. The field cricket, an established model in physiology and behaviour, can provide insights into the effect of ALAN on insect behaviour. The stridulation and locomotion patterns of adult male crickets reared under different lifelong ALAN intensities were monitored simultaneously for five consecutive days in custom-made anechoic chambers. Daily activity periods and acrophases were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
34
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(44 citation statements)
references
References 57 publications
(109 reference statements)
6
34
4
Order By: Relevance
“…There is also a growing literature on the generally adverse effects on orthopteran communication and behaviour caused by anthropogenic factors such as climate change (Cusano et al, 2016), radiation resulting from nuclear accidents (Fuciarelli and Rollo, 2021), artificial light at night (Levy et al, 2021) and urban and traffic noise (e.g. Bent et al, 2021;Gurule-Small and Tinghitella, 2019;Schmidt et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…There is also a growing literature on the generally adverse effects on orthopteran communication and behaviour caused by anthropogenic factors such as climate change (Cusano et al, 2016), radiation resulting from nuclear accidents (Fuciarelli and Rollo, 2021), artificial light at night (Levy et al, 2021) and urban and traffic noise (e.g. Bent et al, 2021;Gurule-Small and Tinghitella, 2019;Schmidt et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Australian populations of Teleogryllus commodus were slow to initiate movement towards calling mates in the presence of ALAN either in the laboratory or under streetlights, but they did engage in sexual behaviour suggesting that ALAN was not entirely detrimental to their reproduction (Thompson et al, 2019). In another example, lifetime rearing of Gryllus bimaculatus (Orthoptera: Gryllidae) under 12 h light and 12 h of ALAN of intensities varying from 2, 5, to 40 lux revealed that although there was a greater impact of higher ALAN intensities, all experimental light intensities at night affected locomotory and stridulatory rhythms (Levy et al, 2021). There was greater asynchrony between individuals in calling activity and locomotion, all of which are likely to have critical effects on mating as well as foraging activity.…”
Section: Effect Of Alan On Nocturnal Insectsmentioning
confidence: 98%
“…Crickets are farmed commercially worldwide, however, the rearing technology varies and depends on many factors, which may affect their development and nutritional profile as for instance rearing environment [22] and diets. Regarding lighting, different light intensity and duration were applied to improve production efficiency [4,23,24]. Various use of rearing materials as conventional (egg carton, cotton wool and plastic bucket) and improvised (bamboo, scrap blanket and plywood-based cage) materials has no effect on their growth [25].…”
Section: Distribution Of Edible Cricketsmentioning
confidence: 99%